Эколого-физиологические особенности популяции непарного шелкопряда (Porthetria dispar L.) в Нижнем Приднепровье. Сообщение I. Структура популяции - Колыбин, В.А.; Зелинская, Л.М. (Вестник зоологии, 1969)
The ecological analysis of Porthetria dispar population structure in the Lower Dnieper area showed that it consists of 4 micropopulations connected with certain fodder plants and isolated during separate stages of a life cycle of the insect. Such dismembering of P. dispar population into separate micropopulations favours the maintenance of the pest quantity and makes the pest control more difficult